A produção de conhecimento sob a lógica do mercado: pesquisa e pós-graduação na Universidade Federal de São Carlos - Fargoni, Everton Henrique Eleutério (Universidade Federal de São Carlos, 2021)
This study aimed to investigate the market potential of research carried out by graduate students with grants funded by the São Paulo State Research Support Foundation in the Graduate Programs of the Center for Exact Sciences and Technology (CCET) at the University Federal of São Carlos (UFSCar). In the set of data collected and analyzed, the five-year period 2015-2020 was considered, considering the research started after 2015 and completed or under development by December 2020. In all, 127 researches were identified, divided into the following levels: master's (37), doctorate (32) direct doctorate (6) and post-doctorate (52). The method used was the case study, a form of research that allowed privileging the work of young researchers in training through data surveys on scientific platforms: FAPESP's Virtual Library, National Directory of Research Groups of the National Council for Scientific Development and Technology (CNPq), the Lattes curriculum and the Research Gate. The results confirmed the hypothesis of the predominance that research developed by graduate students at the CCET, in this case, are directly or indirectly involved with the productive sector. 70.07% of the total researches are being developed with national and international companies. In detail, master (70.27%), doctorate (71.87%), direct doctorate (100%) and post-doctorate (65.38%). Considering the analysis and results of the data, we reflect on the Brazilian political and economic context in recent decades and how the changes in scientific production in Brazil were ordered and, consequently, the crises in the scope of Science and Economics.
The production of knowledge under the logic of the market: research and postgraduate studies at the Universidade Federal de São Carlos
La producción de conocimiento bajo la lógica del mercado: investigación y estudios de posgrado en la Universidade Federal de São Carlos
Keywords: Educação superior; Produção de conhecimento; Pesquisa; Pós-graduação; Higher Education; Knowledge Production; Research; Postgraduate; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO